Smart Street Solutions Using Iot - Ganesh Kumar, E; Anusha, Kandhadai; Saipriya, V; Dass, P (International Journal of Engineering and Technology, 2018)
Street light failure has become a major problem in cities nowadays. As the failure reports are sent very rare to government, these failures are checked only if a higher involvement action takes place. Monitoring of street lights and controlling is of utmost importance in developing country like India. Moreover, in today’s world, power saving is very important and difficult. Though there are many power generation methods, it has become very difficult due to insufficient resources. Considering this as a problem, this project is developed to send accurate location of fuse blown street light to a contact number (if government number provided). When a Street light doesn’t glow even after it is powered ON, the light detector circuit detects which is immediately sent to an Intel® Edison processor which processes the information. A GSM Module is attached to it, which sends the location of the blown fuse street light to the respective contact number.